2018
DOI: 10.1088/1361-6595/aacbf5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrode degradation on the electrical characteristics of surface dielectric barrier discharge

Abstract: Degradation in aluminium and copper foil electrodes in surface dielectric barrier discharges (sDBDs), operating in ambient air, is studied using various microscopic methods. It is determined that difference in the oxidation dynamics for these two materials lead to different morphology of the exposed electrode edge. The structure of the exposed electrode, in its turn, affects the dynamics of the microdischarges and the main integral electrical characteristics of the sDBD: power input, charge amplitude, shape of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…The selection of energy density has been made since this energy has been proved to be the driving force of all the chemical reactions and therefore it directly influences service life 30 . Energy density has been chosen instead of energy because it’s easier to scale it to different kind of electrodes by taking its surface as reference.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of energy density has been made since this energy has been proved to be the driving force of all the chemical reactions and therefore it directly influences service life 30 . Energy density has been chosen instead of energy because it’s easier to scale it to different kind of electrodes by taking its surface as reference.…”
Section: Resultsmentioning
confidence: 99%
“…To Previous work has shown that exposing electrodes to a conductive solution at low frequencies can cause electrode degradation. 54,55 Seen in Figure 4.1, even after many uses at a high frequency, the electrodes in Figure 4.1C have not degraded to the degree of the electrodes in When compared to the new electrodes in Figure 4.1A, the used electrodes have also degraded, though this is expected after multiple uses at high voltages and frequencies. Thus, radio frequency current provides the least electrode degradation and is the preferred frequency range for E-NAAMP.…”
Section: Frequency Effect On Electrode Integritymentioning
confidence: 90%
“…The selection of energy density has been made since this energy has been proved to be the driving force of all the chemical reactions and therefore it directly influences service life [29] . Energy density has been chosen instead of energy because it's easier to scale it to different kind of electrodes by taking its surface as reference.…”
Section: 2-accelerated Degradation Under Corona Discharge Phenomenamentioning
confidence: 99%